Cytoplasmic p27 is a novel prognostic biomarker and oncogenic protein for nasopharyngeal carcinoma. Issue 1 (1st January 2020) - Teng, Yaoshu; Hu, Linping; Yu, Bo; Li, Xiao; Chen, Manman; Fu, Xiao; Zhang, Jin; Gao, Yueqiu; Xu, Rujun; Zhu, Jin
Abstract: Cytoplasmic p27 plays an important role in regulating the cell cycle. Recent studies have revealed p27 protein translocation from the nucleus to the cytoplasm in many tumour cells. The aim of this study was to investigate the role and molecular mechanisms of cytoplasmic p27 in the progression of nasopharyngeal carcinoma (NPC) and to explore its prognostic value. We found increased cytoplasmic p27 expression by immunohistochemistry in NPC tissues, and its expression level was significantly correlated with the T classification and TNM clinical stage of NPC. The survival rate was significantly lower for NPC patients with cytoplasmic p27 immunopositivity than for NPC patients with cytoplasmic p27 immunonegativity, and cytoplasmic p27 was an independent risk factor that affected the prognosis of patients with NPC. Cytoplasmic p27 promoted the proliferation, cell cycle progression, migration, and invasion of NPC cells, increased Bim-1 and Twist1 protein levels, and decreased RhoA-GTP level. Collectively, these findings suggest that cytoplasmic relocalization of p27 is involved in the pathogenesis of NPC and is closely related to the unfavourable prognosis of patients with NPC. Therefore, cytoplasmic p27 might be a useful prognostic factor and potential therapeutic target for patients with NPC.